The Influence of Summarizing Short Stories Towards Students’ Narrative Writing Ability - Nur Amalia Solikhah; Ratna Arum Sari (CV. Tripe Konsultan, 2022)
The objectives of the research are to know and describe the average score of students’ narrative writing ability, and to know and describe whether there is an influence of Summarizing Short Stories towards students’ narrative writing ability at SMP Negeri 8 Bandar Lampung in 2020/2021. Most of the students get difficulties in improving their language skills, especially in writing. Writing is a problem in expressing and developing ideas or thoughts into written form. Narrative text is one of kinds of text that should be learned by the students. To solve the problem above, the writer used the technique in teaching narrative writing that is Summarizing Short Stories. In this research, the writer chooses the title: “The Influence of Summarizing Short Stories towards Students’ Narrative Writing Ability at the Second Semester of the Eighth Class at SMP Negeri 8 Bandar Lampung in 2020/2021”. In this reseach, the writer analyzed the result by using t-test formula. The research was conducted at the eighth class of SMP Negeri 8 Bandar Lampung in 2020/2021. The students of VIIIa were as a sample that were taught by using Summarizing Short Stories. The result of the research showed that there was significant influence of using Summarizing Short Stories towards students’ narrative writing ability. It is shown by the distribution list with df = (n1 + n2 – 2) = (23 + 22 – 2) = 43 obtained ttable t0.95 or significance level of 5% and ttable t0.99 or significance level of 1% was equal to 1.68 and 2.42. there were lower than tcount = 3.84 and the average score of students’ narrative writing ability in experimental class ( =66.58) was higher than the students’ score in control class (: 56.14) at the second semester of the eighth class of SMP Negeri 8 Bandar Lampung in 2020/2021.